Telling business tales with data: A systematic literature review on data storytelling in business analytics - Ruonti, Tiia (My University, 2024)
This thesis presents a systematic literature review on data storytelling in business analytics based on PRISMA guidelines. Data storytelling refers to using narratives and visualizations when communicating insights from data. The purpose of this thesis is to outline the academic literature around this subject and report the key findings on the impacts of data storytelling in business analytics, the practices of data storytelling used by business analytics professionals as well as the enablers of data storytelling in business analytics. The systematic literature review includes 19 articles on the impacts, practices, and enablers of data storytelling in the context of business analytics. Based on the findings, leveraging data storytelling in business analytics can have a positive effect on business performance. One likely reason for this is the improvement of decision-making quality. It was also found that leveraging data storytelling in their work can improve the performance of business analysts. The findings implicate that the leveraging of data storytelling in business analytics is inhibited by insufficient support from visual analytics tools as well as the lack of data storytelling competency and training. The findings highlighted that in order to leverage data storytelling in business analytics, business analysts should understand their target audience as well as business themes and communicate and collaborate with their colleagues and the audience. The findings also discussed suitable data story genres and design principles for the business analytics context.

Tässä Pro gradu -tutkielmassa esitellään PRISMA-ohjeistuksiin perustuva systemaattinen kirjallisuuskatsaus datan tarinankerronnasta bisnesanalytiikassa. Datan tarinankerronnalla tarkoitetaan narratiivien ja visualisointien hyödyntämistä datasta tehtävien havaintojen kommunikoinnissa. Tutkielman tarkoituksena on koota yhteen aiheen akateemista kirjallisuutta sekä esittää keskeisimmät löydökset vaikutuksista, joita datan tarinankerronnan hyödyntäminen bisnesanalytiikassa tuo sekä mitä datan tarinankerronnan käytäntöjä bisnesanalytiikan ammattilaiset työssään käyttävät ja miten datan tarinankerrontaa voidaan hyödyntää bisnesanalytiikassa. Kirjallisuuskatsaukseen sisältyi 19 artikkelia, joissa käsiteltiin datan tarinankerronnan vaikutuksia, käytäntöjä ja hyödyntämistä bisnesanalytiikan kontekstissa. Tutkielman löydösten perusteella datan tarinankerronnan hyödyntäminen bisnesanalytiikassa voi vaikuttaa positiivisesti liiketoiminnan menestykseen. Todennäköisesti yhtenä syynä tähän on päätöksenteon laadun paraneminen. Datan tarinankerronnan hyödyntämisen todettiin myös voivan parantaa bisnesanalyytikkojen suorituskykyä. Löydökset osoittavat myös sen, että datan tarinankerronnan hyödyntämistä bisnesanalytiikassa rajoittavat riittämätön tuki visuaalisilta analytiikkatyökaluilta sekä datan tarinankerronnan taitojen ja koulutuksen puute. Tuloksissa korostui myös se, että datan tarinankerronnan hyödyntämisen mahdollistamiseksi bisnesanalyytikoiden on tärkeää ymmärtää yleisöään sekä liiketoiminnan edellytyksiä ja kommunikoida sekä tehdä yhteistyötä kollegoiden ja yleisön kanssa. Löydöksissä tuli myös esiin bisnesanalytiikan kontekstiin sopivia datatarinoiden genrejä sekä periaatteita datatarinoiden suunnitteluun.
Keywords: data storytelling, data stories, business analytics, systematic literature review